SYNTACTIC ERROR ANALYSIS IN INDONESIA LANGUAGE DESCRIPTIVE ESSAYS OF SEVENTH GRADE STUDENTS AT SMP NEGERI 1 SINDUE TOBATA - Aulia, Ninda; Tahir, Moh; Bismawati, Andi; Juniati, Juniati; Sukma, Sukma (Universitas Muhammadiyah Makassar, 2026)
This study aims to describe the types of syntactic errors found in the descriptive essays of seventh-grade students at SMP Negeri 1 Sindue Tobata. This research employed a descriptive qualitative method, with students’ written works as the data source. The findings show that students’ ability to apply Indonesian syntactic structures still needs improvement. The most frequent errors include phrase structure errors, such as the use of nonstandard phrases, ineffective phrases, and phrases that do not align with their syntactic functions. In addition, sentence structure errors were also identified, including run-on sentences, incomplete sentences, and disorganized sentence elements that obscure meaning. Spelling errors, particularly in the use of capital letters and punctuation marks, further reduced the clarity of students’ writing. These findings indicate that students tend to write using patterns of spoken language, resulting in poorly structured written language. The contributing factors to these errors include limited understanding of phrase concepts and effective sentences, a lack of structured writing practice, and insufficient habituation in applying the rules of Indonesian orthography (PUEBI). Therefore, a more systematic instructional approach is needed to enhance students’ syntactic skills in writing descriptive essays.